Silver Nanowire Membrane: Chinese Knot Inspired Ag Nanowire Membrane for Robust Separation in Water Remediation (Adv. Mater. Interfaces 11/2018). Issue 11 (11th June 2018) - Xiong, Zhu; Li, Tiantian; Liu, Fu; Lin, Haibo; Zhong, Yun; Meng, Qing'an; Fang, Qile; Sakil, Habib; Song, Weijie
Abstract : In article number1800183 by Fu Liu and co‐workers, a Chinese knot inspired Ag nanowire membrane is designed to achieve robust catalytic/anti‐bacterial separation in water remediation. Both PVDF micro‐/nano‐structures and Ag nano‐knots play a crucial role of firmly anchoring the Ag nanowire layer. Chinese knot inspired membranes pave a new avenue for multi‐purpose membrane applications in catalysis and separation.